An activity in rat tissues that modifies nitrotyrosine-containing proteins - Kamisaki, Yoshinori (National Academy of Sciences, 1998)
Homogenates from rat spleen and lung could modify nitrotyrosine-containing BSA. With incubation, nitrotyrosine-containing BSA lost its epitope to a monoclonal antibody that selectively recognized nitrotyrosine-containing proteins. In the presence of protease inhibitors, the loss of the nitrotyrosine epitope occurred without protein degradation and hydrolysis. This activity was found in supernatant but not particulate fractions of spleen homogenates. The factor was heat labile, was sensitive to trypsin treatment, and was retained after passage through a membrane with a 10-kDa retention. The activity was time- and protein-concentration dependent. The activity increased about 2-fold in spleen extracts with endotoxin (bacterial lipopolysaccharide) treatment of animals, suggesting that the activity is inducible or regulatable. Other nitrotyrosine-containing proteins also served as substrates, while free nitrotyrosine and some endogenous nitrotyrosine-containing proteins in tissue extracts were poor substrates. Although the product and possible cofactors for this reaction have not yet been identified, this activity may be a “nitrotyrosine denitrase” that reverses protein nitration and, thus, decreases peroxynitrite toxicity. This activity was not observed in homogenates from rat liver or kidney, suggesting that there may also be some tissue specificity for the apparent denitrase activity.